2011
DOI: 10.1007/s12306-011-0105-z
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the capitate

Abstract: Giant cell tumors are primary bone tumors most often observed in the metaepiphyses of long bones; location in the hand, especially the carpal bones, is rare. We report a patient with recurrent giant cell tumor of the capitate and discuss treatment and prognosis in this rare site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Only 11 cases of GCT of the capitate bone were reported. [2][3][4][5][6][7][8][9][10] In 9 of 11 cases, the radiographic stage according to the Campanacci et al grading system 8 was found (►Table 1). Details of age, gender, radiographic stage, treatment, and, when available, evolution of these 11 cases are given in ►Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Only 11 cases of GCT of the capitate bone were reported. [2][3][4][5][6][7][8][9][10] In 9 of 11 cases, the radiographic stage according to the Campanacci et al grading system 8 was found (►Table 1). Details of age, gender, radiographic stage, treatment, and, when available, evolution of these 11 cases are given in ►Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…For treatment of GCT of carpal bones, care must be taken when using an intralesional curettage with or without bone grafting, and an excisional procedure is recommended to prevent recurrence [1719]. If the scaphoid, lunate, or triquetrum is affected, proximal row carpectomy (PRC) or complete excision of the involved bone combined with an intercarpal fusion is the method of choice [2022].…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor (GCT) accounts for approximately 5% of all tumors in bones. 1 The incidence of GCTs in bones of the hand is estimated to be between 2 and 5%. [1][2][3][4][5][6] However, its occurrence in the carpal bones is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence of GCTs in bones of the hand is estimated to be between 2 and 5%. [1][2][3][4][5][6] However, its occurrence in the carpal bones is extremely rare. There are limited case reports describing the occurrence and treatment of GCTs in the carpal bones, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and a few case reports have described GCT in the capitate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation